An Anatomy of International Trade: Evidence From French Firms - Eaton, Jonathan; Kortum, Samuel; Kramarz, Françis (Econometrica, 2011)
We examine the sales of French manufacturing firms in 113 destinations, including France itself. Several regularities stand out: (i) the number of French firms selling to a market, relative to French market share, increases systematically with market size; (ii) sales distributions are similar across markets of very different size and extent of French participation; (iii) average sales in France rise systematically with selling to less popular markets and to more markets. We adopt a model of firm heterogeneity and export participation which we estimate to match moments of the French data using the method of simulated moments. The results imply that over half the variation across firms in market entry can be attributed to a single dimension of underlying firm heterogeneity: efficiency. Conditional on entry, underlying efficiency accounts for much less of the variation in sales in any given market. We use our results to simulate the effects of a 10 percent counterfactual decline in bilateral trade barriers on French firms. While total French sales rise by around $16 billion (U.S.), sales by the top decile of firms rise by nearly $23 billion (U.S.). Every lower decile experiences a drop in sales, due to selling less at home or exiting altogether.